Effects of Station Buffer Capacity on Performance of Token-Ring Networks - DENG, Robert H. (Institutional Knowledge at Singapore Management University, 1993)
This paper investigates the effects of station buffer capacity on the performance of token ring networks. The network is modelled as a multi-queue system with a single cyclic server, one finite buffer queue and an arbitrary number of infinite buffer queues. Approximate average message delays for both the finite and infinite buffer stations and the probability of message blocking at the finite buffer station are derived, and numerical results are presented. Interesting conclusions are obtained when we compare network performance when the network traffic load is completely balanced with the case when the finite buffer station is much more heavily loaded than the individual infinite buffer stations. The latter situation would arise, for example, in the interconnected networks employing gateways or bridges.